Synergistic Effects of TeO2-SeO2 in Hydroxyapatite Coatings: A Dual Approach to Combat Inflammation and Infection (Journal of Scientific Research, 2024)
This paper introduced the temperature-controlled thermal decomposition method to provide unique nanostructured TeO2-SeO2-HAp coatings on Ti substrates. The mechanical and biological studies, including anti-bacterial and non-cytotoxic properties, are established under various simulated scenarios. In vitro, results indicated that the TeO2-SeO2-HAp coating has excellent adhesion strength and bioactivity. In addition, introducing nano TeO2-SeO2-HAp coatings inhibits the growth of gram-positive bacteria (Staphylococcus aureus) and gram-negative bacteria (Escherichia coli), without resorting to antibiotics. TeO2-SeO2 samples have only 75.99 % inflammation at 200 µg/mL and show excellent anti-inflammatory properties. The TeO2-SeO2-HAp coating reasonably showed good in vitro anti-bacterial as well as anti-inflammatory properties with no significant reduction in cell viability, i.e., at lower dosages of up to 83.09 g/mL. This shows a proof-of-concept for a TeO2-SeO2-HAp coating as a potential non-toxic anti-infective barrier for orthopedic implants with enhanced bio-mechano-functionalities.